An efficiency-based allocation of carbon emissions allowance: A case study in China. (1st April 2020) - Du, Juan; Pan, Meng; Chen, Yao; Duan, Yongrui
Abstract: Tackling the issue of Greenhouse Effect requires global action and a combined international effort from both developed and developing nations. Allocation of the total emissions reduction target among various entities is an issue of both theoretical importance and practical significance. Based on efficiency analysis, this paper proposes a methodology to develop an iterative procedure that can realize the disaggregation of emissions allowance. We use China as a typical case to illustrate our methodology, and disaggregate China's national reduction target of carbon dioxide emissions into targets applicable at the provincial level. Our results indicate that economically well-developed entities exhibit smaller percentages in carbon reductions. In contrast, less-developed entities should lower their carbon emissions by significant amounts, since their economic growth rates do not align with the huge amounts of ecological consumption. By implementing the proposed allocation scheme, the cross-performance of all involved entities will achieve the best state. The proposed method is readily applicable to general scenarios including nations, industries and enterprises. The results could support decision makers in developing an equitable and easy-to-operate allocation scheme of emissions allowance among various entities. The findings from the case study can be generalized to a global level that economic development and emissions status quos affect the scales of emissions reduction. Highlights: A new method is developed to decide how to equitably allocate emissions allowance. The method is applicable to general scenarios like nations, industries and firms. The allocation plan makes all participants achieve the best cross-performance state. Economic development and emissions status quos affect emissions-reducing scales. Findings of the case study in China support the hypotheses and can be generalized.